Universal Design for Learning in postsecondary STEM education for students with disabilities: a systematic literature review - Jillian Schreffler; Eleazar Vasquez III; Jacquelyn Chini; Westley James (SpringerOpen, 2019)
Abstract Universal Design for Learning is not widely used in postsecondary STEM education. The purpose of this literature review is to synthesize the empirical literature using Universal Design for Learning in postsecondary STEM education for all learners. The criteria for this review are (a) empirical literature in (b) peer reviewed journals (c) published after 2006. Keywords used were STEM, UDL/UDI/Universal Design, and postsecondary/university/college/higher education. This review identified four studies and three literature reviews that met the search criteria; the analysis of the identified literature provides a model for how Universal Design for Learning can impact postsecondary STEM instruction, including an increase in inclusive teaching methods and self-advocacy from students with disabilities, and leads to recommendations for additional research.